Persepsi staf akademik Unimas terhadap keberkesanan sistem kehadiran - Abdul Hamid, Adon (Universiti Malaysia Sarawak, 2003)
The aim of the study is to find out the perception of Unimas academic staff towards the defectiveness of attendance system that being used. As absenteeism could cost an organization, monitoring process and the attendance system weaknesses are also identified in the study.